Psychological Well-Being of Al-Qur'an Education School Teachers in Banyuwangi - Fitria, Yuli; Budi, Yulifah Salistia; Damayanti, Fransiska Erna; María-José, Chandrasekaran (World Psychology, 2023)
The profession of Al-Qur'an education school teachers tend to be perceived positively in the community, their role in shaping the positive character of students is a benchmark for success in educating. However, this is a separate demand for them to always be a person who looks perfect so that they do not have the freedom to express themselves which has an impact on their psychological well-being. This study aimed to find out the description of psychological well-being of Al - Qur'an education school teachers in Banyuwangi. The research design was quantitative descriptive analytic. The sampling technique used was purposive sampling with a total of 102 participants. The instrument used a psychological well-being scale (PsychologicalWell-beingScale) which consists of 42 items developed from six dimensions, with a reliability value of 0.883. Statistical analysis used descriptive analysis techniques. The results of the psychological well-being of Al-Qur'an education school teachers based on the late adult age group, female gender, length of teaching and education level up to university level showed the high category with the score ranged from 190 to 205 with a percentage reaching 69%. It could be indicated that there were other factors related to the dimensions of achieving psychological well-being including emotional maturity, experience and knowledge possessed by individuals